2005
DOI: 10.1080/00140130500319757
|View full text |Cite
|
Sign up to set email alerts
|

Interfering effects of the task demands of grip force and mental processing on isometric shoulder strength and muscle activity

Abstract: The purpose of this study was to examine the interfering effects of physical and mental tasks on shoulder isometric strength in different postures. Fifteen volunteers (seven women, eight men) performed a series of isometric shoulder exertions at 30 degrees , 60 degrees and 90 degrees of both shoulder flexion and abduction alone and with the addition of a 30% grip force, a mental task (Stroop test) and both additional tasks simultaneously. The shoulder tasks were completed either at maximal intensity, or while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
35
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 30 publications
4
35
0
Order By: Relevance
“…The addition of gripping decreased deltoid activity by 4-14% of maximum voluntary excitation (MVE) as arm elevation angle increased. Although others have found similar decreases in deltoid activity with gripping, the reaction of the rotator cuff to gripping is not as clear (Antony and Keir, 2009;Smets et al, 2009;Au and Keir, 2007;MacDonell and Keir, 2005). Sporrong et al (1995Sporrong et al ( , 1996 found supraspinatus activity increased by 4-20% MVE while changes to infraspinatus activity were less consistent, in some cases decreasing by as much at 8% MVE while in other cases increasing as much as 21%.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…The addition of gripping decreased deltoid activity by 4-14% of maximum voluntary excitation (MVE) as arm elevation angle increased. Although others have found similar decreases in deltoid activity with gripping, the reaction of the rotator cuff to gripping is not as clear (Antony and Keir, 2009;Smets et al, 2009;Au and Keir, 2007;MacDonell and Keir, 2005). Sporrong et al (1995Sporrong et al ( , 1996 found supraspinatus activity increased by 4-20% MVE while changes to infraspinatus activity were less consistent, in some cases decreasing by as much at 8% MVE while in other cases increasing as much as 21%.…”
Section: Introductionmentioning
confidence: 81%
“…Sporrong et al (1995Sporrong et al ( , 1996 found supraspinatus activity increased by 4-20% MVE while changes to infraspinatus activity were less consistent, in some cases decreasing by as much at 8% MVE while in other cases increasing as much as 21%. MacDonell and Keir (2005) also found infraspinatus activity to decrease by as much as 6.7% MVE with gripping during maximal shoulder exertions. In submaximal dynamic shoulder raises, Antony and Keir (2009) found infraspinatus activity to increase by 2% MVE.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…3a). While much of the research on concurrent demands have focused on low-level static exertions, a few studies have highlighted stronger interference by cognitive demands during high force production (Macdonell and Keir 2005;Zijdewind et al 2006). Although shorter endurance times were observed at 55% MVC during concurrent demand conditions compared to the control [3.09 (1.04) vs. 3.15 (.86)], these differences were not significant.…”
Section: Muscle Endurance and Fatiguementioning
confidence: 96%
“…It could be argued that at low-level exertions, since force output was controlled, participants were able to maintain their exertion (and not overshoot their target) while processing the mental task. However, a few studies have demonstrated that muscular effort decreases during concurrent work at high force levels (Macdonell and Keir 2005;Mehta and Agnew 2011a, b). This interference may be attributed to the simultaneous activation of dorsolateral prefrontal cortex, which has shown increased activity during motor contractions (Dettmers et al 1996) and during cognitive processing (Rowe et al 2000).…”
Section: Introductionmentioning
confidence: 97%